Décrire, est-ce déjà juger ? - Aubrie Jouanno (Terrains/Théories)
Nowadays, the exercise of parental authority is regulated by the government in order to protect « children at risk ». Once they are entrusted to child welfare, judges have to evaluate if children can be sent home or should instead, stay in foster care. But, how can a judge determine if children are still at risk in their family while they do not live there anymore ? This article depicts the collective process of the renewal of an order to place a child in foster care by examining two central tools of the judicial process : the social report sent to the judges and the hearing. Using the method of policy ethnography, the paper shows how the court decision results from the collective construction of the way to judge the children and their parents. In this process, their voices have little chance to be heard otherwise than by being mediated by institutional discourses.